Interferensi Dialek Bahasa Dayak Bakati Dan Dayak Ahe Kalimantan Barat Di Desa Tiang Tanjung Dusun Pandan Kabupaten Landak (Kajian Sosiolinguistik) - FARIDA; NURWAKHID MULIYONO; LULY ZAHROTUL LUTFIYAH (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Language is a means and infrastructure used as a means of everyday communication. Language also plays an important rolefor people to be able to interact with each other. This research aims to obtain information regarding the development and how the process of Dayak Bakati and Dayak Ahe language interference occurs in West Kalimantan Barat in Tiang Tanjung Village, Pandan Hamlet, Landak Regency and to obtain information regarding developments in the use of the Dayak Bakati and Dayak Ahe languages. The formulation of the problem in this research is what is the process of interference in the Dayak Bakati and Dayak Ahe languages in Tiang Tanjung Village, Pandan Hamlet, Landak Regency and what is the influence of interference in the use of the Dayak Bakati and Dayak Ahe languages? This research method uses a qualitative descriptive approach. Data collection techniques were carriedout using interviews, observation and documentation. Based on the research that has been carried out, it can be concluded that there is interference between the dialects of the Dayak Bakati and Dayak Ahe languages in the village of Tiang Tanjung, Dusun Pandan, Landak Regency as a bilingualism community due to language interferencedue to elaboration in the area which has resulted in interference with the Dayak Bakati and Dayak Ahe languages and until now These two languages are the languages used by the Dayak people.